PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU PADA SEKOLAH MENENGAH KEJURUAN NEGERI KOTA SOLOK - Desi Julia Putri (Jurnal Bahana Manajemen Pendidikan, 2017)
The purpose of this research was look information about the student perception about pedagogic kompetence of theacher on vocation senior hight school. This is a descriptive research. The population is 2874 students and research sample is 101 students that taken by simple random sampling. The instrument of this research was a questionnaire with Likert scale models that had tested for validity and reliability. Data analyzed using the average (mean) formula. The resultsof this research show student perception about pedagogic kompetence of theacher on vocation senior hight school (SMKN) in Solok city  stay in  good category with an average score 3,40 become 68 percent.Keywords: Perception, Pedagogic Competence